Who Is the Preferred Tutor in Clinical Skills Training: Physicians, Nurses, or Peers?. Issue 3 (3rd July 2017) - Abay, Ece Şükriye; Turan, Sevgi; Odabaşı, Orhan; Elçin, Melih
ABSTRACT: Phenomenon: Clinical skills centers allow structured training of undergraduate medical students for the acquisition of clinical skills in a simulated environment. Physician, nurse, or peer tutors are employed for training in those centers. All tutors should have appropriate training about the methodology used in the clinical skills training. Many of the studies revealed the effectiveness of various types of tutors. The aim of our study was to evaluate medical students' satisfaction with clinical skills training, and their opinions about the differences in coaching skills among the physician, nurse, and peer tutors. Approach: This study was conducted with third-year students (467 students) in 2013-2014 academic year at Hacettepe University Faculty of Medicine. Participation rate was 85 % (397 students). The students attended the suturing skill training in groups of 40 students. First, a faculty member from the Department of Medical Education delivered a video demonstration and conducted discussion. After the demonstration, the students were divided into groups of 5-6 students. A physician, nurse, or a peer tutor facilitated each group. The students were asked to complete the Coaching Skills Evaluation Form after the practicum session. It contained 13 criteria for assessing the coaching skills. Additionally, the form included a question for rating the student's satisfaction with the tutor. The performance of the tutors at each step was rated on a three-point scale. Findings: Kruskal Wallis analysis was used to compare students' scores for their tutors. The students' satisfaction with tutors was high for all of the tutors. However, there was no difference between students' scores in suturing skill, and between physician, nurse, and peer tutors' coaching skills. Insights: In this study, we revealed that physician, nurse, and peer tutors were equally effective on the students' performances. They were also regarded as effective in their teaching role by students. But the most important point was that sufficient tutor training and preparation was crucial for the success of models.